Photofunctional metal-organic framework thin films for sensing, catalysis and device fabrication - Gomez, Germán Ernesto (2020)
Metal Organic Frameworks (MOFs) constitute a developing class of materials constructed by metallic ions or inorganic clusters bridged by organic ligands, generating 2D or 3D extended porous crystalline structures. Their physical and chemical properties can be dramatically changed since the huge database of metal centers and type of ligands available for the design and construction MOFs. Besides, the implementation of anchored MOF onto different substrates opens up to an emerging field of device fabrication for specific applications. In this review we surveyed the recent progress and developments on MOF for sensing, catalylisis, photovoltaics, up conversion, and LED fabrication.